Walkabout - Roeg, Nicolas, 1928-; Agutter, Jenny; Roeg, Luc; Gumpilil, David; Marshall, James Vance, 1924-; Barry, John, 1933-; Home Vision Cinema; Janus Films; Public Media Incorporated (Wilmette, Ill.) ([Chicago, IL] : Home Vision Cinema/Janus Films (publisher) : Public Media Incorporated (distributor), 1998)
An Australian aborigine on his tribal initiation'walkabout' in the outback rescues an English brother and sister who have been abandoned there
Production design, Brian Watwell ; editors, Antony Gibbs, Alan Pattillo ; music, John Barry
Casts : Jenny Agutter, Lucien John, David Gumpilil
DVD. Dolby digital
Keywords: Marshall, James Vance, 1924- -- Film and video adaptations; Australian aborigines -- Drama; Abandoned children -- Drama; Adventure films; Film adaptations; Video recordings for the hearing impaired; Feature films; Australia -- Drama